2002
DOI: 10.1086/340427
|View full text |Cite
|
Sign up to set email alerts
|

Early Onset of Severe Familial Amyotrophic Lateral Sclerosis with a SOD-1 Mutation: Potential Impact of CNTF as a Candidate Modifier Gene

Abstract: Mutations in the copper/zinc superoxide dismutase 1 (SOD-1) gene are found in approximately 20% of patients with familial amyotrophic lateral sclerosis (FALS), or amyotrophic lateral sclerosis 1. Here we describe a 25-year-old male patient who died from FALS after a rapid disease course of 11 mo. Sequencing of the SOD-1 gene revealed a heterozygous T-->G exchange at position 1513 within exon 5, coding for a V-->G substitution at position 148 of the mature protein. Genetic analysis of this family revealed the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
48
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 105 publications
(49 citation statements)
references
References 46 publications
(71 reference statements)
1
48
0
Order By: Relevance
“…For the population of French origin, the P413L variant conferred a 3.3-fold greater risk to develop ALS. The risk conferred by the P413L CHGB variant is quite robust when compared to other susceptibility genes reported so far (12)(13)(14)(15). In fact, a risk factor of 3.3 is comparable to the overrepresentation by threefold of APOE-4 isoform in Alzheimer's disease patients heterozygous carriers compared to aged healthy control individuals (16)(17)(18).…”
Section: Discussionmentioning
confidence: 66%
“…For the population of French origin, the P413L variant conferred a 3.3-fold greater risk to develop ALS. The risk conferred by the P413L CHGB variant is quite robust when compared to other susceptibility genes reported so far (12)(13)(14)(15). In fact, a risk factor of 3.3 is comparable to the overrepresentation by threefold of APOE-4 isoform in Alzheimer's disease patients heterozygous carriers compared to aged healthy control individuals (16)(17)(18).…”
Section: Discussionmentioning
confidence: 66%
“…Targeted inactivation of the Cntf gene in mice revealed its role in postnatal maintenance of motoneurons (17,18). Moreover, endogenous Cntf modulates onset and severity of disease in patients and mouse models for motoneuron disease and other neurological disorders (19)(20)(21). In progressive motor neuronopathy and wobbler mice, Cntf treatment protects motoneurons from cell death and improves motor performance (22,23), indicating that this factor is a major mediator of the protective effects of Schwann cells, both under physiological and pathological conditions.…”
mentioning
confidence: 99%
“…Faster progression of disease has been reported in patients with a mutation in the ciliary neurotrophic factor (CNTF) gene associated with the SOD1 gene compared than in those who lack the CNTF mutation. 27 The authors concluded that CNTF is a modifier gene that could modulate the progression of the disease, but this finding was not confirmed by other investigators. 28 On the other hand, the vascular endothelial growth factor (VEGF) gene is considered a risk factor for sporadic amyotrophic lateral sclerosis.…”
Section: Discussionmentioning
confidence: 88%